2007
DOI: 10.1007/s00455-007-9101-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Pharyngeal Transit of a Paste Bolus in Chagas’ Disease

Abstract: We measured the oral and pharyngeal transit of a paste bolus in 20 patients with Chagas' disease and 21 controls. Each subject swallowed of a 10-ml paste bolus prepared with 50 ml of water and 4.5 g of instant food thickener labeled with 55.5 MBq of 99m technetium phytate. After the scintigraphic recording of the transit, we delineated regions of interest (ROI) corresponding to mouth, pharynx, and proximal esophagus. Time-activity curves were generated for each ROI. There was no difference between patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 26 publications
3
22
0
6
Order By: Relevance
“…The lingering of pharyngeal residues, found in 18.2% of the patients, is similar to the findings in previous studies, 14,17,18,19 which showed a longer pharynx transit and depuration time in patients with the Chagas disease.…”
Section: Discussionsupporting
confidence: 80%
“…The lingering of pharyngeal residues, found in 18.2% of the patients, is similar to the findings in previous studies, 14,17,18,19 which showed a longer pharynx transit and depuration time in patients with the Chagas disease.…”
Section: Discussionsupporting
confidence: 80%
“…Clearance was the total exposure to the bolus in a ROI, which represents the interval between the arrival of the bolus head into the ROI and the departure of the bolus tail from the ROI. The definition of these ROIs and of the measurements performed were previously described and shown (1,6,7,16) . The statistical analysis of transit and clearance times and the amount of residues was made using a linear model with mixed effects (14) .…”
Section: Methodsmentioning
confidence: 99%
“…However, pharyngeal changes have been demonstrated in these patients. Two studies [6,7] have analyzed the oral and pharyngeal transit in patients with Chagas' disease using the scintigraphic method. With swallows of a liquid bolus the authors found that these patients had a longer oral transit time and longer pharyngeal clearance than healthy subjects [6].…”
Section: Introductionmentioning
confidence: 99%